2017
DOI: 10.18632/oncotarget.21192
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAT1 modulates neuropathic pain progression through sponging miR-155

Abstract: Neuropathic pain is caused by dysfunction or primary injury of the somatosensory nervous system. Long noncoding RNAs (lncRNAs) play important roles in the development of neuropathic pain. However, the effects of lncRNA colon cancer associated transcript-1 (CCAT1) in neuropathic pain have not been reported. The model of bilateral sciatic nerve chronic constriction injuries (bCCI) is regarded as long-lasting mechanical hypersensitivity and cold allodynia, which is the representative symptom in the human subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…miR‐30b can regulate the sodium channel Nav1.7 in rats with neuropathic pain . In addition, lncRNA CCAT1 can regulate neuropathic pain progression by targeting miR‐155 . LncRNA Kcna2 antisense RNA promotes neuropathic pain by inhibiting Kcna2 .…”
Section: Discussionmentioning
confidence: 99%
“…miR‐30b can regulate the sodium channel Nav1.7 in rats with neuropathic pain . In addition, lncRNA CCAT1 can regulate neuropathic pain progression by targeting miR‐155 . LncRNA Kcna2 antisense RNA promotes neuropathic pain by inhibiting Kcna2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that lncRNAs are upregulated or downregulated in some neuropathic pain models. For example, the expression of lncRNA colon cancer-associated transcript-1 (CCAT1) in a neuropathic pain model of bilateral sciatic nerve chronic constriction injuries (bCCI) has been found to be decreased [93]. In this study, lncRNA CCAT1 overexpression was demonstrated to increase pain threshold and reverse cold allodynia in rats.…”
Section: Epigenetics Of Painmentioning
confidence: 70%
“…Yu et al [60] found that silencing of FKBP51 alleviated the mechanical pain threshold and inhibited DRG inflammatory factors and pain mediators through the NF-κB signaling pathway. Dou et al [61] revealed that overexpression of CCAT1 partially alleviated the pain threshold by acting as a sponge for miR-155 through targeting SGK3. SGK3 is an important inflammatory signaling protein that plays a key role in signaling pathways and cellular phosphorylation cascade [62].…”
Section: Other Lncrnasmentioning
confidence: 99%
“…For instance, studies have shown that the MAPK and NF-κB signaling pathways regulated by lncRNAs may be responsible for the majority of inflammatory mediator-signaling actions within nociceptive neurons [54,60,79,80]. The ERK pathway, as a branch of the MAPK signaling pathway, is another main pathway that indicates a relationship between lncRNAs and NP [61,80]. In addition, Zhang et al [81] used Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis and pathway network analysis to disclose differentially expressed genes and activated signaling pathways in association with SCI-induced NP and found that 209 pathways changed significantly; among them, the most significantly activated one is the MAPK signaling pathway.…”
Section: Lncrnas Involved In Signaling Pathways Of Npmentioning
confidence: 99%